Ultrasonographic Measurement of Optic Nerve Sheath Diameter in Preeclamptic and Eclamptic Patients Before and After Anesthetic Management for Cesarean Delivery - Ali Masoud (Khalij-Libya Journal of Dental and Medical Research, 2025)
Preeclampsia and eclampsia are grave obstetric complications where neurological sequelae are linked to elevated intracranial pressure (ICP). Invasive ICP monitoring is the gold standard, but is often contraindicated due to associated risks. Ultrasonographic measurement of the optic nerve sheath diameter (ONSD) has emerged as a promising, non-invasive surrogate for ICP. This study aims to prospectively compare serial ONSD measurements in patients with preeclampsia without severe features versus those with severe preeclampsia/eclampsia undergoing cesarean delivery, and to observe dynamic changes following delivery and anesthetic management. A prospective comparative study will be conducted involving 40 parturients scheduled for elective cesarean section. Participants will be allocated into two groups: Group 1 (Preeclampsia without severe features, n=20) and Group 2 (Severe Preeclampsia/Eclampsia, n=20). ONSD will be measured via transorbital ultrasonography at three time points: pre-operatively, immediately post-operatively, and 6 hours post-delivery. The primary outcome is the change in ONSD over time. Secondary outcomes include the correlation between ONSD and serum biomarkers of preeclampsia severity, and the determination of an optimal ONSD cut-off value for predicting eclampsia risk. This study is expected to provide robust, prospective data on the utility of ONSD as a dynamic, non-invasive monitoring tool for intracranial hypertension in the peripartum management of preeclampsia, potentially informing future clinical guidelines.